Proceedings The International Conference on Industrial Engineering and Business Management (ICIEBM) 2010 - Proceeding... (Department of Industrial Engineering Faculty of Science and Technology UIN Sunan Kalijaga, 2010)
tr,2/nr, c.1-2/ws.c.3